2018
DOI: 10.1103/physrevlett.120.211803
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically Free Natural Supersymmetric Twin Higgs Model

Abstract: Twin Higgs (TH) models explain the absence of new colored particles responsible for natural electroweak symmetry breaking (EWSB). All known ultraviolet completions of TH models require some nonperturbative dynamics below the Planck scale. We propose a supersymmetric model in which the TH mechanism is introduced by a new asymptotically free gauge interaction. The model features natural EWSB for squarks and gluino heavier than 2 TeV even if supersymmetry breaking is mediated around the Planck scale, and has inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…Eq. (36). For any nonvanishing C f the QFP potential behaves as a nonrational power of x at the origin; therefore, its second order derivative at x = 0 is singular for η x > 0.…”
Section: A φ 4 -Dominance Approximationmentioning
confidence: 98%
“…Eq. (36). For any nonvanishing C f the QFP potential behaves as a nonrational power of x at the origin; therefore, its second order derivative at x = 0 is singular for η x > 0.…”
Section: A φ 4 -Dominance Approximationmentioning
confidence: 98%
“…Such decays are not excluded by LHC data at the O(10%) level, motivating v B /v A 3 [65]. At a scale above several TeV, the model can be UV-completed in supersymmetric, extra-dimensional or composite frameworks [66][67][68][69][70][71][72][73][74][75][76]. Unfortunately, the minimal MTH theory gives rise to an unacceptable cosmological history, since the mirror and visible sectors are kept in thermal equilibrium by SM-mirror Higgs mixing until temperatures of a few GeV [55], resulting in a very large ∆N ef f = 5.7 [77,78], in conflict with current bounds [79] Fortunately, there are two simple solutions to this inconsistency, which are illustrative of the collider-cosmology complementarity of hidden sector experimental signatures.…”
Section: Contentsmentioning
confidence: 99%
“…It has been shown that the breaking of the discrete Z 2 symmetry can be realized spontaneously [19][20][21][22][23]. Ultraviolet completions have been constructed based on supersymmetry [24][25][26][27][28][29][30] (see also [31]), compositeness of the Higgs [32][33][34], and most recently using a "turtle" construction [35]. Composite MTH models have been shown to be consistent with precision electroweak constraints [36] and flavor bounds [37], and their collider signals studied [38,39].…”
Section: Introductionmentioning
confidence: 99%